Clinical and microbiological profile of type 2 diabetic patients with urinary tract infections - Deepa, Sandinti; Lakshmaiah, V.; Natarajan, Arvind; K., Prabhakar; A., Raveesha (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes Mellitus is reported to increase the risk of Urinary Tract Infection (UTI) with higher probability of drug resistant organisms. Understanding the burden, microbiological profile and antibiotic sensitivity pattern is vital for effective prevention and management. To assess the microbiological profile and antibiotic sensitivity pattern of Urinary Tract infections among type 2 diabetes mellitus patients. Methods: The study was A prospective observational study done on 117 type 2 diabetic subjects aged above 18 years presenting with symptoms of UTI in a tertiary care hospital Urine was analyzed for urine routine examination, culture and antibiotic sensitivity using standard testing methods on a midstream urine sample. Descriptive analysis was carried out by mean and standard deviation for quantitative variables, frequency and proportion for categorical variables. Results: The mean age of the study population was 57 years. Females constituted 62.39% of participants. Burning micturition (52.99%) was the most common presenting symptom. The prevalence of culture positive UTI was 51.28%. Among gram-negative bacilli, Escherichia coli (20.51%), Klebsiella (6.85%) dominated the culture reports. Enterococcus (4.27%) and Staphylococcus aureus (2.6%) were the common gram-positive organisms isolated. Meropenem was the most effective antibiotic against E. coli (87.5%) and Klebsiella (95%) Vancomycin had 100% sensitivity against Enterococci and S. aureus. Conclusions: More than half of diabetic patients presenting with symptoms of UTI had culture positive UTI, predominantly caused by gram negative organisms. There is a need for comparative studies of Diabetes and controls to explore the key differences in the pattern of UTI.